A holistic approach to animal health research: Increasing livestock production under disease challenge - Irvin, A.D. (1997)
Livestock disease is only one of a number of constraints to improving productivity in smallholder systems, and research is only one approach to alleviating that constraint. However, within the correct context, animal health research that alleviates the constraint of disease can bring enormous benefits, as the example of controlling East Coast fever (ECF) in small-holder dairy systems demonstrates. In this way, ILRI's research not only contributes to improving livestock productivity directly but, through resultant contributions to improving animal health in general, also contributes to wider goals of food security, poverty alleviation, environmental conservation and gender equality - key objectives of developmental aid.